111Indium antimyosin antibody imaging of primary myocardial invovement in systemic diseases. Issue 2 (1st February 1999) - Sarda, L; Assayag, P; Palazzo, E; Vilain, D; Guillevin, L; Faraggi, M; Meyer, O; Le Guludec, D
Abstract : OBJECTIVE: The diagnosis of primary myocardial involvement in systemic diseases is clinically relevant but difficult in the absence of specific criteria. Whatever the underlying disease, myocytes degeneration is observed during the active phase of myocardial damage. The aim of this study was to assess the diagnostic value of scintigraphic imaging with 111 Indium antimyosin antibody (AM), a specific marker of the damaged myocyte, for ongoing myocardial damage related to systemic diseases. METHODS: 40 patients with histologically confirmed systemic diseases were studied. They were classified into two groups according to the presence (group 1, n=30), or the absence (group 2, n=10) of clinical, electrocardiographic (ECG) or echocardiographic signs suggestive of myocardial involvement. Planar and tomographic acquisitions were obtained 48 hours after injection of AM (90 MBq). Rest 201 thallium (Tl) scintigraphy was also performed to assess myocardial perfusion and scarring. Clinical, ECG, and echocardiographic ± scintigraphic evaluations were repeated during follow up (17 ±19 months) in 36 of 40 patients. RESULTS: In group 1, 13 of 30 patients (43%) showed diffuse significant AM uptake throughout the left ventricle (LV), and no or mild Tl abnormality. Two of these were asymptomatic, four had normal ECG, and two had no clinical or echographic LV dysfunction. All patients in group 2 had negative AMA scintigraphy and normal Tl scintigraphy. During follow up of 12 AM positive patients, cardiac status improved after immunosuppressive treatment was intensified in nine cases, worsened in two cases, and remained stable in one. During follow up of 24 AM negative patients, cardiac status remained stable in 23 cases despite treatment not being increased in 20, including two patients with sequellary myocardial involvement. The last patient developed mild LV dysfunction after 36 months. CONCLUSION: AM scintigraphy allows detection of active myocardial damage related to systemic diseases, with increased specificity compared with conventional methods, and increased sensitivity in some cases. Further studies are needed to assess the potential value of AM scintigraphy as a therapeutic guide.